Europeanisation of civil society through the sponsored European publics - Kutay, Acar (Javnost (Ljubljana), 2012)
The EU institutions, particularly the European Commission and the European Economic and Social Committee, have encouraged and sponsored the emergence of non-governmental organisations in Brussels. This strategy has been aimed at mobilising the interests of social actors toward the EU and at helping to reduce the EU's perceived communication deficit. This article first suggests that, when put into practice, this strategy has rather reinforced Europeanisation of social actors. Europeanisation within civil society has been rendered as legitimisation of the European political project and of particular modes of governance. Then, the article proposes an alternative NGO networking model, which stresses the civilising impacts of public spheres instead of the proximity of civil society with political power.
Keywords: Evropa; Europe; European Union; Evropska unija; javna sfera; javnost; civil society; civilna družba; nevladne organizacije; communication; komuniciranje; oblast; authority; democracy; demokracija